Pengelolaan Perpustakaan di SMP Maarif NU Wanasari - Muzfirah, Suci; Septi_Rizqiana_Aji, Adilla; Melani_Sari, Yuni; Tamsikudin, Tamsikudin (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
The purpose of this research is to find out whether this library has met library management standards and whether there are supporting and inhibiting factors in implementing library management standards in the school. This research is a type of qualitative research with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The techniques used in data analysis are data reduction, data presentation and drawing conclusions. Meanwhile, the sources of information in this research are the Head of the Library, the Head of the School and 1 Library Staff. The results of this research show that; 1) Planning the work program in managing the Library at SMP Maarif NU Wanasari is carried out by 1) preparing a work program; 2) organizing the library is carried out through coordination with the head of the library as coordinator in forming the organizational structure and is assisted by 1 staff member on duty; 3) Implementation of the work program in library management in accordance with what was planned at the planning stage; 4) the library carries out supervision every day, reporting library activities every 6 months. And evaluations are carried out at the end of every semester.